Risk stratification of patients with hypoplastic left heart syndrome and intact atrial septum using fetal MRI and echocardiography. (14th June 2020) - Serrano, Ryan M.; Hussain, Sabena; Brown, Brandon; Ebenroth, Eric S.; Farrell, Anne
Abstract: Despite prenatal diagnosis, prenatal intervention, and immediate postnatal intervention, patients with hypoplastic left heart syndrome and intact or highly restrictive atrial septum have the highest risk for mortality. Charts for all infants diagnosed with hypoplastic left heart syndrome from 2009 to 2017 were retrospectively reviewed and compared, including pulmonary vein Doppler patterns on fetal echocardiogram and evidence of pulmonary lymphangiectasia on fetal MRI. Of the 81 newborns with hypoplastic left heart syndrome, we defined two groups. Group 1 patients had an adequate atrial septal communication (n = 69), while Group 2 met criteria for intact/restrictive septum (n = 12). No patient in Group 1 had a type C pulmonary vein Doppler pattern, while no patient in Group 2 had a type A pulmonary vein Doppler pattern. The two patients with pulmonary lymphangiectasia had type C pulmonary vein Doppler pattern and an intact atrial septum and did not survive. Survival to discharge for Group 1 was 83% compared to 58% for Group 2 (p = 0.116). Survival to stage 2 palliation was 71% for Group 1 compared to 50% for Group 2 (p = 0.186). Only 4 of the initial 12 patients from Group 2 are alive, which is an overall survival of 33%. Our experience supports previous evidence that fetal echocardiography can identify those patients with the greatest likelihood for postnatal intervention as well as those at highest risk for mortality. Fetal MRI is a novel imaging modality that may help providers separate patients at highest risk for mortality, regardless of pulmonary vein Doppler pattern.